The TikTok takeover: the unbelievable journey of the world's most addictive app / Norizam Ahmad @ Muhammad - Ahmad@Muhammad, Norizam (Fakulti Perakaunan, 2023)
TikTok, a social media platform that has taken the world by storm, has experienced a meteoric rise to fame since its inception a few years ago. This article explores the evolution of TikTok, examining its global success and impact on popular culture. Additionally, it examines the platform's potential for financial gain and its role in promoting education. By delving into these aspects, we gain an understanding of TikTok's journey and its influence on various spheres of society.